Hypertension from the patient’s perspective: contributions to the care offered by health professionals and self-care – a qualitative study - Leonardo, Felipe; Custódio, Clarissa Garcia; Lira, Débora Paulino de; Ferreira, Dayana de Oliveira; Pavan, Maria Valéria; Almeida, Fernando Antonio de (São Paulo Medical Journal, 2023)
BACKGROUND: Hypertension is the most common disease in primary care settings. Only 30% of cases were adequately controlled. OBJECTIVES: To analyze the knowledge and understanding of patients with hypertension regarding the factors that facilitate and limit adherence to treatment and, based on the results, build specific guidelines on hypertension self-care and control. DESIGN AND SETTING: This qualitative study was conducted in a primary healthcare setting. METHODS: Patients with hypertension who were followed at a primary healthcare unit were interviewed through focus groups, and a qualitative interpretation of their statements according to Bardin’s content analysis was performed. RESULTS: Three focus groups were formed (21 participants), from whose analysis emerged 74 core ideas related to the concept of hypertension, causes of increase in blood pressure, clinical consequences of hypertension, and possible patients’ contributions to help control blood pressure, arising from eating habits, psychosocial conditions, and lifestyle. Patients tend to accept the concept of “high blood pressure” as an inherent condition of the disease in their lives. Eating habits are strongly related to life history and self-perception of health. The association between high blood pressure and nervousness or stress appears to be strong. CONCLUSION: The experience of having “pressure problem” is unique for each person. It is necessary to optimize listening, recognizing that, for the patient to understand what hypertension is and its management, there must be understanding and convergence of proposals, adjustments, and changes in a positive and personalized way. As a result of this study, we implemented educational actions in primary healthcare units.